“Gestión de riesgos mayores en las instalaciones del camal del GAD municipal del cantón Guamote: Plan de Emergencia”. - Yaucan Aucanshala, Edgar Daniel (2017)
The present work is focused on the Institutional Emergency Plan in the GADMCG camal, according to the management process determined by the SGR, this camal is constituted, by a slaughterhouse of bovines, another one of ovines, corrals for reception of animals, Locker rooms, administrative offices, where they house, 16 direct people and 30 indirect ones in average / day. The investigation was carried out through visits to the mentioned facilities, where it was found, the lack of means of protection, indispensable to strengthen the organizational capacity in the event of an emergency. The meseri method, the nfpa for fires and other formats established by the SGR was elaborated, a map of evacuation, protocols of general emergency, fire and earthquake, also was made a script of simulacrum and material for trainings, spread the importance To implement the emergency plan to 50% of the personnel that will be linked in the camal, did not conformed, or trained the work brigades, nor implemented the means of protection, nor was the drill, because of the clousure of the camal, Initially for three months, with the date of suspension, on April 15, 2015, estimated time for the remodeling of physical work and equipment, the progress of the physical work is suspended and is estimated to reopen in January 2017. It is worth the commitment of the Mayor and the willingness of the USST technician of the GADMCG to implement this plan, thus demonstrating compliance with obligations, professionalism and humanistic commitment to the community.